Euripides. Iphigenia among the Taurians. Bacchae. Iphigenia at Aulis. Rhesus. Translated with Explanatory Notes by James Morwood. With Introduction by Edith Hall, Oxford, Oxford University Press, 1999, liii + 227 pp. - Schamun, María Cecilia (2000)
Fil: Schamun, María Cecilia. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.